Auxinic Herbicide Mixtures for Controlling Multiple Herbicide-Resistant Kochia in Fallow - V. Kumar; T. Lambert; R. Liu; R. S. Currie; P. W. Stahlman (Kansas Agricultural Experiment Station Research Reports, 2021)
Kochia resistant to glyphosate (Roundup), chlorsulfuron (Glean), and dicamba (Banvel or Clarity) has become quite common in the U.S. Great Plains, whereas multiple resistance to additional herbicides, including fluroxypyr (Starane Ultra), atrazine (AAtrex), and metribuzin (Sencor) has also been reported recently. Effective management of these multiple herbicide-resistant (MHR) kochia populations warrants the need of alternative herbicide strategies. The main objective of this research was to investigate the efficacy of auxinic herbicides, including Duplosan (dichlorprop-p), Weedone (2,4-D), Clash (dicamba), and/or Pixxaro (premix of halauxifen and fluroxypyr) alone or in various combinations for controlling MHR kochia. Separate greenhouse and field experiments were conducted at the Kansas State University Agricultural Research Center (KSU-ARC) in Hays, KS. Greenhouse studies included an MHR kochia population (resistant to glyphosate, dicamba, fluroxypyr, chlorsulfuron, atrazine, and metribuzin) from Garden City, KS, and a susceptible (SUS) kochia population from Hays, KS. The postemergence (POST) applied herbicide programs, including Clash Weedone, Duplosan alone or in tank-mix combinations were tested. Field experiments were conducted in a fallow field at KSU-ARC with a natural infestation of kochia population with multiple resistance to glyphosate and dicamba. Herbicides, including Duplosan, Weedone, Clash, and Pixxaro were tested alone or in tank-mix combinations. Results from greenhouse study indicated that Clash, Duplosan, and Weedone applied alone provided inadequate control (5 to 42%) of MHR kochia at 21 days after treatment (DAT). In contrast, control of SUS population was 83 to 92% with Clash and Duplosan alone treatments. Tank-mixing Duplosan with Clash and/or Clash + Weedone significantly improved visible control (72 to 90%) of MHR kochia as compared to Duplosan, Clash, or Weedone alone treatments. Similarly, tank-mixing Clash to Duplosan or Pixxaro (two-way mixtures) and to Duplosan + Weedone, Pixxaro + Duplosan or Pixxaro + Weedone (three-way mixtures), provided an excellent control (91 to 97%) of MHR kochia compared to Clash, Pixxaro, Weedone, and Duplosan alone treatments in a field study. Altogether, these results suggest that tankmixing Clash with Duplosan and/or Pixxaro can potentially provide synergistic effect in controlling MHR kochia in fallow fields.
Keywords: auxinic herbicides; fallow; kochia; multiple herbicide resistance; POST herbicides